Contingent belief updating - Chiara Aina; Andrea Amelio; Katharina Brütt (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
We study how contingent thinking - that is, reasoning through all possible contingencies without knowing which is realized - affects belief updating. According to the Bayesian benchmark, beliefs updated after exposure to new information should be equivalent to beliefs assessed for the contingency of receiving such information. Using an experiment, we decompose the effect of contingent thinking on belief updating into two components: (1) hypothetical thinking (updating on a piece of not-yet-observed information) and (2) contrast reasoning (comparing multiple contingencies during the updating process). Our results show that contingent thinking increases deviations from Bayesian updating and that this effect can be attributed to hypothetical thinking.
Keywords: C91; D83; D91; 330; Belief Updating; Contingent Thinking; Experiment